Pengaruh Bokashi Ela Sagu Pada Berbagai Tingkat Kematangan Dan Pupuk SP-36 Terhadap Serapan P Dan Pertumbuhan Jagung (Zea mays L.) Pada Tanah Ultisol - Margaret Ch Soplanit; Ruddi Soplanit (Agrologia, 2012)
Fertilization efficiency which could enhance soil productivity is determined by type, application method and appropriate dose of fertilizers.  A green house experiment to study effect of different maturity level of ela  sago bokashi and some dosage of  SP-36 fertilizer on P-uptake and growth of maize (zea mays l.) on ultisols has been performed. The experiment was set up in three-replicates factorial Randomized Block Design. The treatments were  three maturity level of ela sago bokashi i.e. 2, 3 and 4 weeks; and four dosages of SP-36 fertilizer i.e. 0, 2, 4 and 6 g/10 kg of soil. The results showed that application of bokashi regardless of their maturity at the same time with each  doses of SP-36  increased P uptake, plant height and stem diameter of maize. Giving four-week ela sago bokashi with 6 gr/10 kg of soil of SP-36 was the best treatment to improve P uptake, plant height and stem diameter of corn crop up to  0.15%, 140, 60 cm and 1.64 mm respectively.